Congenital chylothorax: Conservative management counts - Smriti Bhagiratha; Prathik Bandiya; Niranjan Shivanna; Naveen Benakappa (Wolters Kluwer Medknow Publications, 2022)
Nonimmune hydrops is a common cause of hydrops fetalis. Here, we report a rare case of congenital chylothorax which presented with nonimmune hydrops and was effectively managed by conservative measures.